Carbon-Footprint Policy Of The Top Ten Global Retailers: Contribution To Sustainable Development - Carmen Bălan (Amfiteatru Economic Journal, 2010)
The goal of the article is to study the policy of the most prominent ten global retailers relative to the reduction in their carbon footprint. This policy is an integral part of the environmental component of the organizational policy for sustainable development. The research has an exploratory character and is based on the analysis of public information available on the Internet about the objectives, strategies and achievements of the top ten global retailers in the field of carbon-footprint. According to the research objectives, the main results of the study reveal: the organizations that have sustainable development objectives and policies as well as carbon-footprint objectives and policies; the strategies applied for the reduction in their carbon footprint and the results obtained. Are the top ten global retailers a benchmark as regards the carbon-footprint policies? Do they represent a model which has to be followed by other retailers? Several answers may be found in the present article.
Keywords: M1; M16; 330; sustainable development; environmental assessment; ecological footprint; carbon footprint; greenhouse gas emissions; global retailers